Estimation of a nonseparable heterogenous demand function with shape restrictions and Berkson errors - Richard W. Blundell; Joel Horowitz; Matthias Parey (Centre for Microdata Methods and Practice (cemmap), 2018)
Berkson errors are commonplace in empirical microeconomics and occur whenever we observe an average in a specified group rather than the true individual value. In consumer demand this form of measurement error is present because the price an individual pays is often measured by the average price paid by individuals in a specified group (e.g., a county). We show the importance of such measurement errors for the estimation of demand in a setting with nonseparable unobserved heterogeneity. We develop a consistent estimator using external information on the true distribution of prices. Examining the demand for gasoline in the U.S., accounting for Berkson errors is found to be quantitatively important for estimating price effects and for welfare calculations. Imposing the Slutsky shape constraint greatly reduces the sensitivity to Berkson errors.
Keywords: C14; C21; D12; 330; consumer demand; nonseparable models; quantile regression; measurement error; gasoline demand; Berkson errors